Efectividad de un Programa educativo y Conocimiento Materno Sobre Lactancia Materna, Huamachuco - Alayo Gurronero, Fiorella Altagracia (2015)
This research was carried out in order to establish the degree of relationship between the type of School Lunch box with the nutritional status of children of 03 and 04 years old of School No. 81 658 of Huascar, Jequetepeque in Pacasmayo province of La Libertad region, Peru, because of a diagnosis worrying about feeding conditions of children in the peruvian coastal rural context and how they affect the construction of learning in schools.The sample universe was composed by 35 children. Applied two instruments as Inventary for type of school lunch box (LCPTLE, in spanish) and card of nutritional status in childrens (FRPDENN, in spanish).The obtained information was tabulated, processed in SPSS version 17 and presented in tables of simple and double entry with numerical and percentage frequencies, as well as in graphs. The analysis of the relation of the factors, there were realized by means of the test of independence criterial square Chi (X2). Finding the following conclusions: Of all children (as) has 28,6% have type lunchbox unhealthy and 71,4% have the kind of healthy lunchbox. According to the P/T, 88,6% had normal nutritional status, 5,7% were undernourished and 5,7% were overweight. Also, depending on the indicator T/E, 69.6% had normal height in nutritional status, 85,7% had short stature and the remaining 14,3. Finally, according to the P/E, 88,6% had normal status, 5,7% were undernourished and 5,7% were overweight KEYWORDS: Nutritional status, school lunch box.